Multimodal Cohesion of Luka Bekavac’s Collection Galerija Likovnih Umjetnosti u Osijeku - Buljubašić Srb, Ivana (Anafora, 2024)
Luka Bekavac’s oeuvre Galerija likovnih umjetnosti u Osijeku: studije, ruševine (2017) stands out due to its departure from the genre of the novel and the establishment of the text as a collection of short stories. However, that this is not a conventional collection of short stories in which the texts function completely autonomously, is notable by, among other things, the titular, recurring motif, the narrator, the visual and design choices, which contribute more than other narrative elements to multimodal cohesion. Considering the specific format, design, and typographic-compositional layout of the book, this paper uses the methodological tools of multimodal stylistics to explore and interpret how multimodal cohesion develops in the collection.